Effect of the type of bunches bagging practice in some chemical and physiological characteristics of the fruits of the date palm and orchid palm varieties - Wahab, Nabil Ibrahim Abdel; Mahmoud, Rend Mahmoud Abdel Ghafour (Journal of agricultural, environmental and veterinary sciences, 2018)
This Study was carried out in Khales- Diyala province in national orchard. During growth season 2016 on two cultivars (Khestawi and zahdi), the aim was to investigate the effect of bunches bagging practice with used six types of bags (control, clear polyethylene, green perforated polyethylene, perforated cloth, brown cheese cloth, white cheese cloth) to reducing the effect of high temperature degree, reducing wrinkle and dropping fruits and increase fruit water content. • Fruit chemical characteristic: the bunches bagging had no significantly effect on fruit water content in CV. Khestawi. The bunches bagging treatments had no Significant effect was recorded in C. V. Zahdi. No Significant effect was recorded in tannins in both cultivars. • 2. Fruit physiological characteristic: bunches bagging treatments didn’t effected on fruits maturity and fruits damaged in both cultivars, the bunches bagging of clear polyethylene had Significant decreased dropping fruits in CV. Khestawi, but no Significant effect was recorded about dropping fruits in C. V. Zahdi.